Pengaruh Program Beasiswa Pemuda Tangguh Surabaya Terhadap Tingkat Kesejahteraan Masyarakat - Rahmah, Nadia Nur; Wafi, Muhammad Hibatul; Nisa, Nadia Azzahratun; Falasifah, Nihlatul (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study uses the students of UIN Sunan Ampel Surabaya as a case study to assess the effect of the Surabaya Resilient Youth Scholarship Program on the level of community welfare. The Surabaya City Government created this program to help young people who are talented but do not have the money to go to high school. This study uses a survey-based quantitative method. One hundred student scholarship recipients were asked to participate as respondents. Data was collected through in-depth interviews and questionnaires to evaluate the relationship between the scholarship award and changes in the recipients' socio-economic welfare. The results showed that the program had a positive impact on access to education, meeting basic needs, and developing work skills. In addition, 87% of respondents said that their quality of life had improved since receiving the scholarship, mainly because they were able to reduce the economic burden on their families. In addition, recipients are motivated by the program to participate in community service activities, which has a double impact on community development. However, limited recipient quotas and administrative issues hinder the sustainability of the program. According to this study, the Surabaya Resilient Youth Scholarship Program improves community welfare by strengthening human resources